My name is Shaft: Three times Shaft as a popular-cultural icon (Sociologisk Forskning, 2020)
The character of Shaft has taken shape in different times of political polarization of the American society. The aim of this article is to closer examine how the character Shaft is portrayed in three different movies, from different decades. The analysis is specifically pointed towards how Shaft is positioned in relation to time (the time when the film plays out), place (place in urban space) and race (the African-American community). The three Shaft movies plays out in very different times: 1971, 2000 and 2019, that is, during the civil rights movement and active African-American protests, during a period of neoliberal ideals, and in current times, with heightened polarization and strongly voiced Black Lives Matter protests.
Keywords: Shaft; representation; popular culture; race; class; family; African-American; Blaxploitation